Rhizobacterial Candidates Isolated from Jerusalem Artichoke (Helianthus tuberosus L.) Rhizosphere for Host Plant Growth Promotion - Kamon Sritongon (Science Faculty of Chiang Mai University, 2019)
The objective of this work was to isolate and characterize rhizobacteria from Jerusalem artichoke in order to evaluate their abilities to promote early growth of the plant in vivo. Characterization of plant growth promoting activities such as nitrogen fixation, phosphate and potassium solubilization, indole-acetic acid production (IAA), siderophore and phytopathogenic inhibition was conducted. A total of 46 isolates gave positive results for either direct or indirect plant growth promoting activity. Selected stains were identified on the basis of 16s rRNA gene sequences, evaluated individually by being mixed in liquid media which was then used to inoculate pots containing Jerusalem artichoke. Strains identified as Pseudomonas azotoformans (N3-903 and C2-114) and Rhodococcus cercidiphylli (S1-903) were evaluated in pot experiments under greenhouse conditions. Inoculation of strain C2-114 showed increased shoot dry weight (up to 52.6%), root dry weight (up to 58.5%), and biomass (up to 54.7%). The result of association of IAA activity with plant growth was significant. We provide the first report of plant growth promoting activity by R. cercidiphylli. Pseudomonas strains has the potential to be use in field-grown Jerusalem artichoke.